ANALISIS PERUBAHAN PENGATURAN HUKUM KEWARGANEGARAAN GANDA BAGI DIASPORA INDONESIA DITINJAU DARI PERSPEKTIF UNDANG-UNDANG NOMOR 12 TAHUN 2006 - MZ, H. ISMAIL (GANEC SWARA, 2018)
The need for dual citizenship regulation is an issue that continues to be striven by Indonesian diaspora in various parts of the world dual citizenship has become the dreams of Indonesian diasporas, because until now citizens of Indonesia who live abroad only have  single citizenship status. It is resulted in difficulties and obstacles for the diaspora because of the unequal slowdown and equivalent of citizens present in the access of opportunities.        The emergence of demands for change and dual citizenship of diaspora living abroad, inviting government attention to their aspirations should be heard to serve as input and consideration for the Government and the House of Representatives in the revision or amendment of Law Number 12 of 2006. Dual citizenship is not really the only factor to be able to empower all the diaspora's potential for the country of origin. Therefore the most important thing is how the Government of the country of origin can make efforts in capturing the potential of Indonesia Diaspors scattered in various countries in the world for the benefit of the state and people of Indonesia. Thus, multiple citizenship arrangements in Indonesian citizenship politics become very important to be appreciated and accommodated by the Government and the House of Representatives as a representative who fights for the interests and aspirations of their people whenever and wherever they are in accordance with the mandatory of the constitution of the Republic of Indonesia